A ANALISIS KELAYAKAN MODEL BIOMEDIS EKSPERIMENTAL PADA KASUS DIABETES MELLITUS MENGGUNAKAN MODEL ORGANISME IKAN ZEBRA (Danio rerio) - A. Yashilva, Willy; Septia Rosdiana, Delita; Syafina, Indira Aulia; Cahyadi, Yusuf; Hendroyono, Farrah Lula Klarissa (STIKes Mitra Keluarga, 2024)
Introduction : Animal models are essential for research into diabetes, as they allow scientists to study the disease in a controlled environment. Small freshwater fish known as zebrafish (Danio rerio) are being employed more and more as model organisms in studying human diseases. They are genetically similar to humans, and they share many of the same metabolic pathways. This study aims to assess the viability of utilizing zebrafish as a model organism in the study of diabetes mellitus. Method: This study was examined in three databases, including Google Scholar, PubMed, and Scopus, and 19 publications were included. For that database, we ran the following search query in the titles. A literature review was performed in this study, and Prisma flow diagrams were employed to enhance the clarity and transparency of the review process. A method for summarizing the characteristics of the Zebrafish that make it a desirable model organism for Diabetes Mellitus research. Result: The findings of this study show that zebrafish may be used to investigate the genetics, development, and treatment of diabetes since their glucose metabolism and reactive metabolite production pathways are remarkably similar to those of humans. Similar findings were made regarding the functional conservation in adipose biology, pancreatic anatomy, lipid metabolism, and glucose homeostasis. Conclusion:The conclusion of this study is that the Zebrafish can be used as one of the animal models for identifying new targets for the precaution and medication of diabetes mellitus.